METABOLISM DISORDERS IN CHRONIC NUTRITIONAL DISORDER WITH ACUTE INTESTINAL INFECTION IN PREMIUM CHILDREN - Sidikova Maryam Amankeldievna (Web of Journals Publishing, 2024)
Chronic nutritional disorder (dystrophy) takes a significant place among the pathologies of early-aged children, and it causes a decrease in the body's resistance to infectious diseases, immune reactivity, and endangers the child's health and life. As a result of severe dystrophy (hypotrophy 1st, 2nd, 3rd degree, paratrophy) in early children, it causes the child to lag behind in neuro-spiritual and intellectual development [1,4,9,11,14,21,23].